Effects of different fermentation methods on chemical composition, antioxidant activity, and enzymatic inhibition of fermented fig juice - Peilin Yao; Suyuan Zhao; Lulu Cheng; Chuanping Zhao (CyTA - Journal of Food)
In order to develop nutritious and healthy fermented fig juice, foure samples fermented were made using natural fermentation and fermentation by lactobacillus. Then the total acidity, total sugar, reducing sugar, total phenols, total flavones and characteristic organic acids, antioxidant activity, and inhibition of enzyme activity in fermented fig juice were compared. The results showed that natural fermentation could produce more reducing sugar, lactic acid, flavonoids, and exhibit stronger DPPH radical scavenging capacity and total reducing power. Inhibition of tyrosinase and pancreatic lipase was detected in fermented fig juice, of which the inhibition rate of tyrosinase by natural fermentation was 81.80%, and the inhibition rate of pancreatic lipase by mixed cultures was 38.72%, which was higher than that of other groups. The results indicated the functional activity of fermented fig juice could be improved by fermentation, and the natural fermentation method was found superior.